A new species of Endecous Saussure, 1878 (Orthoptera, Gryllidae) from northeast Brazil with the first X1X20 chromosomal sex system in Gryllidae - Zefa, Edison; Redü, Darlan Rutz; Da Costa, Maria Kátia Matiotti; Fontanetti, Carmem S.; Gottschalk, Marco Silva; Padilha, Giovanna Boff; Silva, Anelise Fernandes E; Martins, Luciano De P. (Zootaxa, 2014)
In this paper we describe a new species of Luzarinae cricket collected from the cave “Gruta de Ubajara, municipality of Ubajara, State of Ceará, Brazil, highlighting phallic sclerites morphology and chromosome complement as diagnostic characters. We presented meiotic and mitotic characterization in order to define the karyotype with 2n = 12 + X1X2♂/12 + X1X1X2X2♀. This represents the first record of X1X20 chromosomal sex system in Gryllidae.